2023
DOI: 10.1186/s13058-023-01645-0
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture for chemotherapy-associated insomnia in breast cancer patients: an assessor-participant blinded, randomized, sham-controlled trial

Abstract: Background Insomnia is a highly prevalent symptom occurred during and post-chemotherapy. Acupuncture may have beneficial effects in the management of chemotherapy-associated insomnia. This study was conducted to determine the efficacy and safety of acupuncture in improving chemotherapy-associated insomnia in breast cancer patients. Methods This assessor-participant blinded, randomized, sham-controlled trial was conducted from November 2019 to Janua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 73 publications
1
9
0
Order By: Relevance
“…Finally, another limitation of this study is that the point selections are all fixed. In some previous clinical studies ( 30 , 61 ), the acupuncture group was selected on an individualized basis using semi-individualized, reflecting the strict adherence to TCM norms of evidence-based treatment for the specific symptoms of the participants. However, these shortcomings will be further improved in future clinical trials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, another limitation of this study is that the point selections are all fixed. In some previous clinical studies ( 30 , 61 ), the acupuncture group was selected on an individualized basis using semi-individualized, reflecting the strict adherence to TCM norms of evidence-based treatment for the specific symptoms of the participants. However, these shortcomings will be further improved in future clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that acupuncture can increase sleep quality while addressing symptoms of mental and emotional distress ( 28 ). Additionally, acupuncture is now being used to improve patients’ sleep problems in cancer centers ( 29 , 30 ). Although there have been a few clinical reports about acupuncture for cancer-caused insomnia ( 31 33 ), these studies fail to classify different types of cancer, and have small sample sizes, or the subjects come from a single center.…”
Section: Background and Objectivementioning
confidence: 99%
“…The seven-item questionnaire uses a 0-4 scale, yielding a total score range of 0-28. Scores correspond to absence (0-7), mild (8)(9)(10)(11)(12)(13)(14), moderate (15)(16)(17)(18)(19)(20)(21), or severe (22-28) insomnia. The ISI is a concise, reliable tool commonly employed in general practice, sensitive to treatment response (14).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the comparisons with positive drugs should be interpreted with caution as these agents are not specifically targeted for sleep-related conditions. Moreover, studies have revealed that acupuncture treatment can improve sleep onset latency, total sleep time, and sleep efficiency; however, compared to sham control, acupuncture does not exhibit a significant difference in reducing ISI ( 21 ). Therefore, the confirmation of acupuncture’s superiority over sham control remains unresolved.…”
Section: Discussionmentioning
confidence: 99%
“…Adverse events are defined as any new untoward medical event (symptoms, side-effect, or reaction) in a patient after interventions. This study will not be monitored by an independent data and safety monitoring committee because acupuncture or sham acupuncture is considered a minimal-risk study in numerous clinical trials and that they were not associated with any serious AEs, low frequency of low-grade AEs potentially related to acupuncture was observed during our previous studies [ 25 , 26 ]. Any AE-related data will be collected by questioning the patient after each treatment or self-reported by participants within 24 h. AEs will be reported electronically within 5 calendar days.…”
Section: Methodsmentioning
confidence: 99%